Method for recycling by-product foamed ceramic through flotation gold tailing recleaning

Foamed ceramic materials are prepared through steps such as shaking table gravity separation, silicon carbide grinding, slaked lime granulation and composite gold leaching, which solves the problem of insufficient gold recovery in gold tailings and achieves efficient utilization of tailings and improvement of material performance.

CN120733864APending Publication Date: 2025-10-03河北省地质实验测试中心(国土资源部保定矿产资源监督检测中心 河北省金银宝玉饰品质量监督检验站)
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511104403.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-07
Publication Date
2025-10-03

AI Technical Summary

Technical Problem

Existing technologies cannot effectively recover gold from gold tailings and result in large tailings discharge, serious waste of resources, and insufficient utilization of gold resources when preparing building materials from tailings.

Method used

The foamed ceramic material is prepared by adopting the steps of shaking table gravity separation, silicon carbide mixed grinding, slaked lime spray granulation, composite gold leaching agent gold leaching and aging, roller forming, drying and sintering to achieve efficient gold recovery and resource utilization of tailings.

Benefits of technology

It achieves efficient recovery of gold in tailings, reduces tailings stockpiles, lowers maintenance costs, and produces excellent foamed ceramic materials with high porosity, low thermal conductivity and good thermal insulation properties, reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120733864A_ABST
    Figure CN120733864A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of comprehensive recycling of tailing resources, and provides a method for recycling a byproduct foamed ceramic through flotation gold tailing recleaning. The flotation gold tailing ore pulp is subjected to shaking table gravity separation, shaking table gravity separation concentrate is returned to a separation plant for mineral separation operation, shaking table gravity separation tailings are concentrated and dehydrated, and concentrated overflow water and concentrated underflow are obtained; the concentrated underflow and silicon carbide are mixed and ground, then slaked lime is doped for spray granulation, and tailing particles are obtained; performing gold leaching operation on the tailing particles by adopting a composite gold leaching agent aqueous solution to obtain a gold-containing pregnant solution and leaching residues, and performing gold separation on the gold-containing pregnant solution to obtain recovered gold and a barren solution; the leaching residues are subjected to aging, roll forming, drying and sintering in sequence, and the foamed ceramic material is obtained. According to the method, recovery of gold in the tailings and large consumption of the flotation gold tailings can be achieved at the same time, the problems that in the prior art, the tailings discharge amount is large, and gold resources in the tailings are seriously wasted are solved, and overall high-value utilization of the flotation gold tailings is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of comprehensive recovery and utilization of tailings resources, in particular to a method for recovering by-product foamed ceramics from flotation gold tailings. Background Art

[0002] Most existing mineral processing plants use a single flotation method to recover gold, generating large quantities of gold tailings with a gold grade of approximately 0.5g / t. Currently, these plants face a range of challenges, including insufficient tailings pond capacity, high maintenance costs, land occupation, and environmental pollution. Therefore, comprehensive utilization of these gold tailings is urgently needed.

[0003] Currently, the comprehensive utilization of gold tailings resources primarily involves tailings filling, tailings re-processing, and the production of building materials. Tailings filling consumes significant amounts of gold tailings, but also requires cement and other binders, increasing costs while generating relatively low added value and insignificant economic benefits. Tailings re-processing methods primarily include gravity separation, flotation, and cyanidation. In practical applications, the appropriate beneficiation method must be selected based on the gold's occurrence state and particle size distribution within the tailings. However, even after re-processing, significant amounts of solid waste are still generated, failing to fundamentally address the problem of high tailings discharge. Tailings production for building materials can consume significant amounts of gold tailings and potentially increase their added value. However, current research has shown that the proportion of gold tailings incorporated into building materials typically ranges from 45% to 80%, resulting in a low utilization rate. Furthermore, to meet the performance requirements of building materials, clay or other materials are often added, increasing the complexity of the process. Furthermore, the crucial, high-value gold element in the tailings remains largely unavailable for effective utilization and extraction. In summary, simply recovering gold from tailings cannot solve the problem of large tailings emissions; and directly using gold tailings to prepare building materials will cause serious waste of gold resources.

[0004] Therefore, there is an urgent need to provide a method that can effectively recover gold from gold tailings and realize the consumption of a large amount of gold tailings. Summary of the Invention

[0005] In view of this, the present invention provides a method for recovering by-product foamed ceramics from flotation gold tailings to solve the problem that the existing comprehensive utilization method of flotation gold tailings resources cannot simultaneously recover gold from the tailings and consumes a large amount of gold tailings.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The present invention provides a method for recovering by-product foamed ceramics from flotation gold tailings, comprising the following steps:

[0008] 1) The flotation gold tailings slurry is subjected to shaking table gravity separation, and the shaking table gravity separation concentrate is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings are concentrated and dehydrated to obtain concentrated overflow water and concentrated underflow;

[0009] 2) mixing the concentrated underflow with silicon carbide and grinding them to obtain a mixed slurry;

[0010] 3) adding slaked lime to the mixed slurry for spray granulation to obtain tailings particles;

[0011] 4) Using a composite gold leaching agent aqueous solution to leaching the tailings particles for gold, obtaining a gold-containing precious liquid and leaching residue; after gold separation from the gold-containing precious liquid, recovered gold and barren liquid are obtained;

[0012] 5) The leached residue is sequentially aged, roll-formed, dried and sintered to obtain a foamed ceramic material.

[0013] Preferably, the mass concentration of the flotation gold tailings slurry in step 1) is 30%; the components of the flotation gold tailings include quartz, feldspar, calcite and chlorite; the mass concentration of the concentrated underflow is 60-65%; and the shaking table gravity separation concentrate is gold-containing sulfide.

[0014] Preferably, the mass ratio of the concentrated underflow to silicon carbide in step 2) is 1:0.001-0.004; and the content of solid particles with a fineness of ≤0.074 mm in the mixed slurry is 93-98%.

[0015] Preferably, in step 3), the mass ratio of the mixed slurry to slaked lime is 1:0.003-0.008; and the particle size of the tailings particles is 4-10 mm.

[0016] Preferably, the gold leaching operation in step 4) is specifically as follows: piling the tailings particles, and then spraying them with a composite gold leaching agent aqueous solution to obtain a gold-containing precious liquid and leaching residue; the thickness of the piling is 50 to 60 cm; the spraying speed is 100 to 150 mL / min, and the time is 2 to 5 days.

[0017] Preferably, the gold separation in step 4) is specifically as follows: the gold-containing precious liquid is adsorbed by activated carbon to obtain gold-loaded carbon and a barren liquid; the volume mass ratio of the gold-containing precious liquid to the activated carbon is 100:1-5; the adsorption time is 12-24 hours; and the barren liquid is recycled as a composite gold leaching agent aqueous solution.

[0018] Preferably, the aging time in step 5) is 3 to 5 days; the moisture content of the aged leaching residue is 8 to 10%; the pressure of the roller forming is 10 to 25 MPa; the drying temperature is 50° C. and the drying time is 20 to 30 hours.

[0019] Preferably, the sintering in step 5) is specifically as follows: placing the dried leached residue in a high-temperature furnace and heating it to 300°C at a rate of 5°C / min and keeping it for 30 minutes; then heating it to 1000-1100°C at a rate of 10°C / min and keeping it for 60-90 minutes; then cooling it to 700°C at a rate of 15°C / min and keeping it for 30 minutes; and finally naturally cooling it to room temperature to obtain a foamed ceramic material.

[0020] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. The method for reselecting and recovering by-product foamed ceramics from flotation gold tailings of the present invention can simultaneously achieve the recovery of gold from tailings and the consumption of a large amount of flotation gold tailings, thereby solving the problem of large tailings discharge and serious waste of gold resources in the tailings, and realizing high-value utilization of flotation gold tailings. At the same time, the method of the present invention does not discharge solid waste or liquid waste during the reselection and recovery process, and most of the gold in the tailings is recovered. While increasing gold production, it reduces the tailings stockpile and saves the maintenance cost of the tailings pond, thus having excellent economic and social benefits.

[0022] 2. The method of the present invention strengthens grinding by adding silicon carbide as a grinding aid, which promotes the exposure and semi-exposure of fine-grained gold minerals, and then adopts the granulation heap leaching method to achieve the dissociation and effective recovery of gold. In addition, the leaching residue after gold extraction by the method of the present invention has fine particle size and high activity, which meets the raw material requirements for preparing foamed ceramics. The added silicon carbide grinding aid will generate gas during the sintering process of preparing foamed ceramics, which acts as a foaming agent and is very suitable for preparing foamed ceramic materials. In addition, the method of the present invention can also decompose residual agents in the leaching process during the molding and sintering of the leaching residue, eliminating the hidden danger of residual agents polluting the environment.

[0023] 3. The method for recovering foamed ceramics from the byproduct of flotation gold tailings, described herein, utilizes the leaching residue produced during the gold recovery process to successfully produce a foamed ceramic material with excellent performance. This material exhibits extremely high porosity, excellent compressive strength, low thermal conductivity, a neat and uniform appearance, and excellent thermal insulation properties. This method not only fully utilizes the leaching residue recovered from flotation gold tailings, maximizing the excellent performance of the foamed ceramic material, but also significantly reduces the raw material cost during the foamed ceramic preparation process and effectively lowers the sintering temperature, achieving dual improvements in resource utilization and cost control. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.

[0025] Figure 1 This is a cross-sectional morphology of the foamed ceramic material prepared in Example 1. DETAILED DESCRIPTION

[0026] The present invention provides a method for recovering by-product foamed ceramics from flotation gold tailings, comprising the following steps:

[0027] 1) The flotation gold tailings slurry is subjected to shaking table gravity separation, and the shaking table gravity separation concentrate is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings are concentrated and dehydrated to obtain concentrated overflow water and concentrated underflow;

[0028] 2) mixing the concentrated underflow with silicon carbide and grinding them to obtain a mixed slurry;

[0029] 3) adding slaked lime to the mixed slurry for spray granulation to obtain tailings particles;

[0030] 4) Using a composite gold leaching agent aqueous solution to leaching the tailings particles for gold, obtaining a gold-containing precious liquid and leaching residue; after gold separation from the gold-containing precious liquid, recovered gold and barren liquid are obtained;

[0031] 5) The leached residue is sequentially aged, roll-formed, dried and sintered to obtain a foamed ceramic material.

[0032] In the present invention, the mass concentration of the flotation gold tailings slurry in step 1) is 30%; the components of the flotation gold tailings include quartz, feldspar, calcite and chlorite.

[0033] In the present invention, the mass concentration of the concentrated underflow in step 1) is 60-65%, preferably 61-64%, and more preferably 62-63%; the shaking table gravity separation concentrate is gold-containing sulfide, preferably pyrite sulfide; and the concentrated overflow water is returned to the ore dressing plant for use as return water.

[0034] In the present invention, the mass ratio of the concentrated underflow to silicon carbide in step 2) is 1:0.001-0.004, preferably 1:0.002-0.004, and more preferably 1:0.003; the content of solid particle fineness ≤0.074 mm in the mixed slurry is 93-98%, preferably 94-97%, and more preferably 96%.

[0035] In the present invention, the silicon carbide in step 2) has a particle size of ≤0.074 mm and a content of 95%. It has a hard texture and acts as a grinding aid during the grinding process, which is beneficial to the complete dissociation or semi-dissociation of the fine gold particles wrapped by the gangue.

[0036] In the present invention, the mass ratio of the mixed slurry to slaked lime in step 3) is 1:0.003-0.008, preferably 1:0.004-0.007, and more preferably 1:0.005.

[0037] In the present invention, slaked lime CaO first reacts with water in the mixed slurry to generate Ca(OH)2, and then reacts with CO2 in the air to generate CaCO3 during the spray granulation process, which helps to increase the hardness of the tailings particles. Part of the unreacted Ca(OH)2 and the generated CaCO3 are hydrolyzed during the gold extraction process, providing an alkaline environment.

[0038] In the present invention, the particle size of the tailings particles in step 3) is 4 to 10 mm, preferably 6 to 8 mm, and more preferably 7 mm; the moisture content of the tailings particles is preferably 5 to 6%; and the condensed water from the spray granulation is returned to the ore dressing plant for use as return water.

[0039] In the present invention, the composite gold leaching agent in the composite gold leaching agent aqueous solution in step 4) is prepared by the method for preparing a composite gold leaching agent in Chinese invention patent CN104372178B; the composite gold leaching agent has the characteristic of low toxicity.

[0040] In the present invention, the mass concentration of the composite gold leaching agent aqueous solution in step 4) is preferably 0.1-0.4%, more preferably 0.1-0.2%, and even more preferably 0.15%.

[0041] In the present invention, the gold leaching operation in step 4) is specifically as follows: piling the tailings particles, and then spraying them with a composite gold leaching agent aqueous solution to obtain a gold-containing precious liquid and leaching residue.

[0042] In the present invention, the heaping is preferably performed as follows: first, a 1 mm thick plastic film is laid on the leaching site as a waterproof layer, a 10 mm thick polyurethane dehydration screen is placed thereon, and then the tailings particles are spread flat on the polyurethane dehydration screen to obtain a ore heap; the leaching site is preferably an open space with a slope of 15°; the heaping increases the uniformity and air permeability during the gold extraction process, which is beneficial to the leaching of gold.

[0043] In the present invention, the thickness of the ore pile is 50 to 60 cm, preferably 52 to 58 cm, more preferably 53 to 56 cm, and more preferably 55 cm; the spraying speed is 100 to 150 mL / min, preferably 110 to 130 mL / min, and more preferably 120 mL / min; the spraying time is 2 to 5 days, preferably 3 to 4 days.

[0044] In the present invention, the spraying is preferably performed by continuously spraying the ore pile with the composite gold leaching agent aqueous solution through a spray hose with holes and placed spirally on the ore pile; the spray hose is also covered with a layer of plastic film to prevent the spray of the composite gold leaching agent aqueous solution from leaking out.

[0045] In the present invention, the gold separation in step 4) is specifically as follows: the gold-containing precious liquid is adsorbed by activated carbon to obtain gold-loaded carbon and a barren liquid; the volume-to-mass ratio of the gold-containing precious liquid to the activated carbon is 100:1-5, preferably 100:2-4, and more preferably 100:3; wherein the activated carbon is preferably gold-adsorbing activated carbon; the adsorption time is 12-24 hours, preferably 13-20 hours, further preferably 14-18 hours, and more preferably 15 hours; the barren liquid is recycled as a composite gold leaching agent aqueous solution.

[0046] In the present invention, the leaching residue in step 4) has formed the characteristics of fine particle size and uniform distribution during the tailings grinding process; the main mineral components of the leaching residue preferably include feldspar and quartz, which can be used as natural raw materials for sintering ceramic materials.

[0047] In the present invention, the aging time in step 5) is 3 to 5 days, preferably 3.5 to 4.5 days, and more preferably 4 days; the moisture content of the leaching residue after aging is 8 to 10%, preferably 8.2 to 9.5%, more preferably 8.5 to 9.3%, and more preferably 8.8 to 9%.

[0048] In the present invention, the roller forming in step 5) roller-presses the aged leached residue to obtain a uniform and regular-sized green body; the main mineral components of the green body preferably include SiO2, Al2O3, CaO, MgO, Fe2O3, TiO2, K2O and Na2O; wherein the total content of SiO2, Al2O3 and CaO is preferably 75-90%, more preferably 80-85%, and more preferably 83%; the pressure of the roller forming is 10-25 MPa, preferably 11-20 MPa, more preferably 12-15 MPa, and more preferably 13 MPa.

[0049] In the present invention, the drying temperature in step 5) is 50° C., and the drying time is 20 to 30 hours, preferably 21 to 28 hours, more preferably 22 to 25 hours, and even more preferably 24 hours.

[0050] In the present invention, the sintering in step 5) is specifically as follows: placing the dried leached residue in a high-temperature furnace and heating it to 300°C at a rate of 5°C / min and keeping it for 30 minutes; then heating it to 1000-1100°C at a rate of 10°C / min and keeping it for 60-90 minutes; then cooling it to 700°C at a rate of 15°C / min and keeping it for 30 minutes; and finally naturally cooling it to room temperature to obtain a foamed ceramic material.

[0051] In the present invention, the leached residue produced during the sintering process in step 5) has a high reactivity and begins to exhibit a liquid phase between 1000° C. and 1050° C. The silicon carbide grinding aid, the calcium carbonate produced during the spray granulation process, and the calcite present in the tailings begin to decompose and produce gas between 1000° C. and 1050° C., i.e., the temperature at which the liquid phase appears in the leached residue is consistent with the temperature at which the foaming agent produces gas.

[0052] In the present invention, the smoke and dust waste gas generated during the sintering process in step 5) is returned to the centrifugal sprayer in the spray granulation process for recycling.

[0053] The technical solutions provided by the present invention are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0054] Example 1

[0055] 1) The flotation gold tailings slurry with a mass concentration of 30% is subjected to shaking table gravity separation using a double-layer shaking table. The shaking table gravity separation concentrate (pyrite sulfide) is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings enter the thickener for concentration and dehydration to obtain concentrated overflow water and concentrated underflow with a mass concentration of 65%. Among them, the concentrated overflow water is returned to the beneficiation plant for use as return water;

[0056] 2) The concentrated underflow and silicon carbide are mixed in a mass ratio of 1:0.001 and then put into a ball mill for grinding to obtain a mixed slurry with a solid particle size of ≤0.074 mm and a content of 94%;

[0057] 3) The mixed slurry is transported to the pump pool and slaked lime is added according to the mass ratio of mixed slurry to slaked lime = 1:0.003. After mixing, it is pumped into the top nozzle of the centrifugal sprayer for spray granulation to obtain tailings particles with a particle size of 5mm and a moisture content of 5%. At the same time, the condensed water generated by the spray granulation is collected and returned to the mineral processing plant for use as return water;

[0058] 4) First, a 1mm thick plastic film is laid on an open space with a slope of 15° as a waterproof layer, and a 10mm thick polyurethane dewatering screen is placed on it. Then, the tailings particles obtained in step 3) are used to build a 0.5m thick ore pile (2m long and 1m wide) on the polyurethane dewatering screen. Then, a spray hose with holes is placed on the ore pile in a spiral shape, and then a layer of plastic film is covered on the spray hose. At the same time, urea, calcium oxide, sodium bicarbonate, sodium tripolyphosphate, aluminum oxide, and ammonium chloride are fully stirred and mixed in a mass ratio of 680:150:190:10:2:10, and then added to a stainless steel high-temperature furnace and heated to 850°C for pyrolysis reaction. After the raw materials in the furnace are completely melted, After the pyrolysis reaction is completed, the material is immediately discharged and cooled naturally. After cooling, a composite gold leaching agent is obtained, and then water is added to prepare a composite gold leaching agent aqueous solution with a mass concentration of 0.1%, which is set aside; the composite gold leaching agent aqueous solution is then used to continuously spray the ore pile at a rate of 120 mL / min for 2 days through a spray hose with holes to obtain a gold-containing precious liquid and leaching residue, and the gold grade in the gold tailings is reduced to 0.15 g / t; the collected gold-containing precious liquid is adsorbed on gold-adsorbed activated carbon for 12 hours and then filtered to obtain gold-containing carbon and barren liquid, wherein the volume mass ratio of the gold-containing precious liquid to the gold-adsorbed activated carbon is 100:1, and the barren liquid is returned to the spray system as water for the composite gold leaching agent aqueous solution and continues to be recycled;

[0059] 5) The leaching residue obtained in step 4) is aged for 3 days to obtain a leaching residue with a moisture content of 10%, and then the aged leaching residue is placed in a roller press and roll-formed at a pressure of 10 MPa to obtain a 600 mm × 600 mm × 16 mm green body. The green body is then placed in an insulation box and dried at 50°C for 24 hours. The dried green body is then placed in a high-temperature furnace for sintering, first raising the temperature to 300°C at a rate of 5°C / min and holding for 30 minutes; then raising the temperature to 1000°C at a rate of 10°C / min and holding for 80 minutes; then lowering the temperature to 700°C at a rate of 15°C / min and holding for 30 minutes; finally, naturally cooling to room temperature to obtain a foamed ceramic material, wherein the smoke and exhaust gas generated during the sintering process is fed into the bottom of the centrifugal sprayer as hot gas for drying.

[0060] In this embodiment, the leaching rate of the precious gold solution is 70%, and the recovered gold obtained from each ton of gold tailings is 0.30 g. This is because the adsorption rate, electrolysis rate, smelting and other factors also cause a 13% gold loss rate.

[0061] In addition, the performance of the foamed ceramics prepared in this embodiment was also tested, among which the water absorption rate, porosity and apparent density were all tested according to the standard of GB / T 3810.3-2016 "Test method for ceramic tiles", the compressive strength was tested according to the standard of GB / T 1964-1996 "Test method for compressive strength of porous ceramics", and the thermal conductivity was tested according to the standard of GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of insulating materials - Protective hot plate method".

[0062] The results show that the foamed ceramic obtained in this example has a volume water absorption rate of 2.3%, a porosity of 85.5%, and an apparent density of 0.34 g / cm 3 , the compressive strength is 1.3 MPa, and the thermal conductivity is 0.12 W / (m·K). That is, the foamed ceramic prepared by the method of the present invention has the characteristics of uniform closed pores, high porosity, high strength and low thermal conductivity, and meets the performance requirements of unglazed foamed ceramic insulation boards in "JG / T511-2017 Foamed Ceramic Insulation Boards for Buildings".

[0063] Example 2

[0064] 1) The flotation gold tailings slurry with a mass concentration of 30% is subjected to shaking table gravity separation using a double-layer shaking table. The shaking table gravity separation concentrate (pyrite sulfide) is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings enter the thickener for concentration and dehydration to obtain concentrated overflow water and concentrated underflow with a mass concentration of 60%. Among them, the concentrated overflow water is returned to the beneficiation plant for use as return water;

[0065] 2) The concentrated underflow and silicon carbide are mixed in a mass ratio of 1:0.004 and then put into a ball mill for grinding to obtain a mixed slurry with a solid particle fineness of ≤0.074 mm and a content of 98%;

[0066] 3) The mixed slurry is transported to the pump pool and slaked lime is added according to the mass ratio of mixed slurry to slaked lime = 1:0.008. After mixing, it is pumped into the top nozzle of the centrifugal sprayer for spray granulation to obtain tailings particles with a particle size of 10mm and a moisture content of 5%. At the same time, the condensed water generated by the spray granulation is collected and returned to the mineral processing plant for use as return water;

[0067] 4) First, a 1mm thick plastic film is laid on an open space with a slope of 15° as a waterproof layer, and a 10mm thick polyurethane dewatering screen is placed on it. Then, the tailings particles obtained in step 3) are built on the polyurethane dewatering screen to form a 0.6m thick ore pile (2m long and 1m wide), and then a spray hose with holes is spirally placed on the ore pile, and then a layer of plastic film is covered on the spray hose; at the same time, urea, calcium oxide, sodium bicarbonate, sodium tripolyphosphate, aluminum oxide, and ammonium chloride are fully stirred and mixed in a mass ratio of 690:150:190:10:2:10, and then added to a stainless steel high-temperature furnace and heated to 850°C for pyrolysis reaction. After the raw materials in the furnace are completely melted, the pyrolysis reaction is initiated. After completion, the material is immediately discharged and cooled naturally. After cooling, a composite gold leaching agent is obtained, and then water is added to prepare a composite gold leaching agent aqueous solution with a mass concentration of 0.4%, which is set aside; the composite gold leaching agent aqueous solution is then used to continuously spray the ore pile at a speed of 150 mL / min for 5 days through a spray hose with holes to obtain a gold-containing precious liquid and leaching residue, and the gold grade in the gold tailings is reduced from 0.50 g / t to 0.10 g / t; the collected gold-containing precious liquid is adsorbed on gold-adsorbed activated carbon for 24 hours and then filtered to obtain gold-containing carbon and barren liquid, wherein the volume mass ratio of the gold-containing precious liquid to the gold-adsorbed activated carbon is 100:5, and the barren liquid is returned to the spray system as water for the composite gold leaching agent aqueous solution and continues to be recycled;

[0068] 5) The leaching residue obtained in step 4) is aged for 3 days to obtain a leaching residue with a moisture content of 10%, and then the aged leaching residue is placed in a roller press and roll-formed at a pressure of 25 MPa to obtain a 600 mm × 600 mm × 16 mm green body. The green body is then placed in an insulation box and dried at 50°C for 30 hours. The dried green body is then placed in a high-temperature furnace for sintering, first raising the temperature to 300°C at a rate of 5°C / min and holding for 30 minutes; then raising the temperature to 1100°C at a rate of 10°C / min and holding for 80 minutes; then lowering the temperature to 700°C at a rate of 15°C / min and holding for 30 minutes; finally, naturally cooling to room temperature to obtain a foamed ceramic material, wherein the smoke and exhaust gas generated during the sintering process is fed into the bottom of the centrifugal sprayer as hot gas for drying.

[0069] In this embodiment, the leaching rate of the precious gold solution is 80%, and the recovered gold obtained from each ton of gold tailings is 0.35 g. This is because the adsorption rate, electrolysis rate, smelting and other factors also cause a 13% gold loss rate.

[0070] In addition, the performance of the foamed ceramics prepared in this embodiment was also tested, among which the water absorption rate, porosity and apparent density were all tested according to the standard of GB / T 3810.3-2016 "Test method for ceramic tiles", the compressive strength was tested according to the standard of GB / T 1964-1996 "Test method for compressive strength of porous ceramics", and the thermal conductivity was tested according to the standard of GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of insulating materials - Protective hot plate method".

[0071] The results show that the foamed ceramic obtained in this example has a volume water absorption rate of 2.5%, a porosity of 87.0%, and an apparent density of 0.30 g / cm 3 The compressive strength is 1.2MPa, the thermal conductivity is 0.11W / (m·K), and it has the characteristics of uniform closed cells, high porosity, high strength and low thermal conductivity, meeting the performance requirements of unglazed foamed ceramic insulation boards in "JG / T511-2017 Foamed Ceramic Insulation Boards for Buildings".

[0072] Example 3

[0073] 1) The flotation gold tailings slurry with a mass concentration of 30% is subjected to shaking table gravity separation using a double-layer shaking table. The shaking table gravity separation concentrate (pyrite sulfide) is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings enter the thickener for concentration and dehydration to obtain concentrated overflow water and concentrated underflow with a mass concentration of 65%. Among them, the concentrated overflow water is returned to the beneficiation plant for use as return water;

[0074] 2) mixing the concentrated underflow with silicon carbide in a mass ratio of 1:0.003 and grinding the mixture in a ball mill to obtain a mixed slurry having a solid particle size of ≤0.074 mm and a content of 96.8%;

[0075] 3) The mixed slurry is transported to the pump pool and slaked lime is added according to the mass ratio of mixed slurry to slaked lime = 1:0.005. After mixing, it is pumped into the top nozzle of the centrifugal sprayer for spray granulation to obtain tailings particles with a particle size of 7mm and a moisture content of 5%. At the same time, the condensed water generated by the spray granulation is collected and returned to the mineral processing plant for use as return water;

[0076] 4) First, a 1mm thick plastic film is laid on an open space with a slope of 15° as a waterproof layer, and a 10mm thick polyurethane dewatering screen is placed on it. Then, the tailings particles obtained in step 4) are used to build a 0.55m thick ore pile (2m long and 1m wide) on the polyurethane dewatering screen. Then, a spray hose with holes is placed on the ore pile in a spiral shape, and then a layer of plastic film is covered on the spray hose. At the same time, urea, calcium oxide, sodium bicarbonate, sodium tripolyphosphate, aluminum oxide, and ammonium chloride are fully stirred and mixed in a mass ratio of 700:150:190:10:2:10, and then added to a stainless steel high-temperature furnace and heated to 850°C for pyrolysis reaction. After the raw materials in the furnace are completely melted, After the pyrolysis reaction is completed, the material is immediately discharged and cooled naturally. After cooling, a composite gold leaching agent is obtained, and then water is added to prepare a composite gold leaching agent aqueous solution with a mass concentration of 0.2%, which is set aside; the composite gold leaching agent aqueous solution is then used to continuously spray the ore pile at a rate of 120 mL / min for 3 days through a spray hose with holes to obtain a gold-containing precious liquid and leaching residue, and the gold grade in the gold tailings is reduced to 0.11 g / t; the collected gold-containing precious liquid is adsorbed on gold-adsorbed activated carbon for 15 hours and then filtered to obtain gold-containing carbon and barren liquid, wherein the volume mass ratio of the gold-containing precious liquid to the gold-adsorbed activated carbon is 100:1, and the barren liquid is returned to the spray system as water for the composite gold leaching agent aqueous solution and continues to be recycled;

[0077] 5) The leaching residue obtained in step 4) is aged for 3 days to obtain a leaching residue with a moisture content of 10%, and then the aged leaching residue is placed in a roller press and roll-formed at a pressure of 12 MPa to obtain a 600 mm × 600 mm × 16 mm green body. The green body is then placed in an insulation box and dried at 50°C for 24 hours. The dried green body is then placed in a high-temperature furnace for sintering, first raising the temperature to 300°C at a rate of 5°C / min and holding for 30 minutes; then raising the temperature to 1050°C at a rate of 10°C / min and holding for 70 minutes; then lowering the temperature to 700°C at a rate of 15°C / min and holding for 30 minutes; finally, naturally cooling to room temperature to obtain a foamed ceramic material, wherein the smoke and exhaust gas generated during the sintering process is fed from the bottom of the centrifugal sprayer as hot gas for drying.

[0078] In this embodiment, the leaching rate of the precious gold solution is 70%, and the recovered gold obtained from each ton of gold tailings is 0.30 g.

[0079] In addition, the performance of the foamed ceramics prepared in this embodiment was also tested, among which the water absorption rate, porosity and apparent density were all tested according to the standard of GB / T 3810.3-2016 "Test method for ceramic tiles", the compressive strength was tested according to the standard of GB / T 1964-1996 "Test method for compressive strength of porous ceramics", and the thermal conductivity was tested according to the standard of GB / T10294-2008 "Determination of steady-state thermal resistance and related properties of insulating materials - Protective hot plate method".

[0080] The results show that the foamed ceramic obtained in this example has a volume water absorption rate of 2.5%, a porosity of 86.5%, and an apparent density of 0.31 g / cm 3 The compressive strength is 1.23MPa, the thermal conductivity is 0.10W / (m·K), and it has the characteristics of uniform closed cells, high porosity, high strength and low thermal conductivity, meeting the performance requirements of unglazed foamed ceramic insulation boards in "JG / T511-2017 Foamed Ceramic Insulation Boards for Buildings".

[0081] The foamed ceramic prepared in this embodiment was cut, and the cross-sectional morphology is shown in FIG. Figure 1 As shown, from Figure 1 It can be seen that the bubbles inside the foamed ceramic are complete, independent and evenly distributed, which shows that the sintering system of the present invention can obtain foamed ceramic materials with excellent performance.

[0082] In summary, the method of the present invention can recover most of the gold in the flotation gold tailings, and the foamed ceramic material prepared from the leaching residue generated during the recovery process can be used as a building insulation material, achieving the effect of taking into account both economic and environmental benefits.

[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for recovering by-product foamed ceramics from flotation gold tailings, characterized in that: The steps include: 1) The flotation gold tailings slurry is subjected to shaking table gravity separation, and the shaking table gravity separation concentrate is returned to the beneficiation plant for beneficiation operations. The shaking table gravity separation tailings are concentrated and dehydrated to obtain concentrated overflow water and concentrated underflow; 2) mixing the concentrated underflow with silicon carbide and grinding them to obtain a mixed slurry; 3) adding slaked lime to the mixed slurry for spray granulation to obtain tailings particles; 4) Using a composite gold leaching agent aqueous solution to leaching the tailings particles for gold, obtaining a gold-containing precious liquid and leaching residue; after gold separation from the gold-containing precious liquid, recovered gold and barren liquid are obtained; 5) The leached residue is sequentially aged, roll-formed, dried and sintered to obtain a foamed ceramic material.

2. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 1, wherein: The mass concentration of the flotation gold tailings slurry in step 1) is 30%; The flotation gold tailings contain quartz, feldspar, calcite and chlorite; The mass concentration of the concentrated underflow is 60-65%; The shaking table gravity separation concentrate is gold-containing sulfide.

3. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 2, wherein: The mass ratio of the concentrated underflow to silicon carbide in step 2) is 1:0.001-0.004; The content of solid particles with a fineness of ≤0.074 mm in the mixed slurry is 93-98%.

4. The method for recovering by-product foamed ceramics from flotation gold tailings according to any one of claims 1 to 3, characterized in that: The mass ratio of the mixed slurry to slaked lime in step 3) is 1:0.003-0.008; The particle size of the tailings particles is 4 to 10 mm.

5. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 4, wherein: The gold leaching operation in step 4) is specifically as follows: the tailings particles are piled up, and then sprayed with a composite gold leaching agent aqueous solution to obtain a gold-containing precious liquid and leaching residue; The thickness of the pile is 50 to 60 cm; The spraying speed is 100-150 mL / min, and the time is 2-5 days.

6. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 5, wherein: The gold separation in step 4) is specifically as follows: the gold-containing precious liquid is adsorbed by activated carbon to obtain gold-loaded carbon and barren liquid; The volume mass ratio of the precious liquid to the activated carbon is 100:1-5; The adsorption time is 12 to 24 hours; The barren solution is circulated and used as water for composite gold leaching agent aqueous solution.

7. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 6, wherein: The aging time in step 5) is 3 to 5 days; the moisture content of the leached residue after aging is 8 to 10%; The pressure of the roll forming is 10 to 25 MPa; The drying temperature is 50° C. and the drying time is 20 to 30 hours.

8. The method for recovering by-product foamed ceramics from flotation gold tailings according to claim 7, wherein: The sintering in step 5) is specifically as follows: placing the dried leached residue in a high-temperature furnace and heating it to 300°C at a rate of 5°C / min and holding it for 30 minutes; then heating it to 1000-1100°C at a rate of 10°C / min and holding it for 60-90 minutes; then cooling it to 700°C at a rate of 15°C / min and holding it for 30 minutes; and finally naturally cooling it to room temperature to obtain a foamed ceramic material.

Citation Information

Patent Citations

  • Composite gold leaching agent and its preparation method

    CN104372178B